Measurement of Attenuation Coefficients of Near Surface Material Using SASW Method - Suharsono S (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
The spectral analysis of surface waves (SASW) is an in situ non-destructive method. It has been developed and used for many years in the fields of geotechnical engineering and site characterization. It is typically used in evaluation of elastic moduli and layer thickness of soils, rocks and pavements.In this study the SASW was used to measure an attenuation coefficient (α) of near surface material at 15 development sites with different material e.i. soils, granite and methamorphics rock.. The attenuation coefficient which is the exponential decay constant of the amplitude of surface wavepropagation was approximated by Bornitz equation. The amplitude of vertical ground surface vibration generated by impact tests on the ground surface was measured at various radial distances.A good empirical correlation between the measured attenuation coefficients and the corresponding shear modulus and SPT or RQD data were established. These results suggest that the attenuation coefficient could be used as an alternative parameter for characterization of near surface material. Based on this method, the subsurface material at sites the study can be classified into two groups.The first group represented a low stiffness material with attenuation values of greater than 0.00516 s/m and the second group was a high stiffness material with attenuation values of less than 0.00150 s/m.However, this method of evaluation was still in development stage and needs to be substantiated with more results of measurements.